Editorial - Mendes, Enicéia Gonçalves; Matos, Selma Norberto; Reis dos Santos, José Jackson; Campos Pereira, Sandra Márcia (Práxis Educacional, 2014)
Apresenta, em linhas gerais, o conteúdo deste número da revista.